Intercultural communicative competence among Indonesian migrant workers in Malaysia: a qualitative exploration - Djatmika,; Mohamad, Bahtiar; Santosa, Riyadi; Wibowo, Agus Hari (Frontiers in Sociology, 2024)
Millions of Indonesian migrant workers have sought employment in Malaysia during the last three decades. Many of them are skilled and unskilled laborers, and their incorporation into the host society’s labor market has the potential to improve their own quality of life while also contributing significantly to the country’s economy. However, Indonesian migrant workers encounter numerous problems in their professional and personal lives. Therefore, this study aims to investigate the intercultural communicative competence (ICC) factors as one of the Indonesian migrant workers’ strategies. This is qualitative exploratory research on the factors of ICC in the integration of Indonesian migrant workers into the Malaysian labor market. Focus groups were used to obtain data from 16 Indonesian migrant workers who had already successfully integrated into the Malaysian workforce as well as newcomers who were in the process of integrating into the local culture. In addition, interviews have been conducted with the 13 employers to complement the data from the migrant workers. The data was analyzed using rounds of deductive and inductive coding and analysis based on the five components of Byram’s model. The findings suggest that practicing intercultural communication skills can help migrant employees overcome cultural difficulties in the Malaysian labor market. The Indonesian migrant workers and their employers also indicated that they have an advantage in cultural integration due to the cultural similarities. The paper discusses the implications of the findings in terms of ICC training offered to migrant workers themselves (culture and language) and to professionals who work with them, with the goal of facilitating and promoting Indonesian migrant workers’ labor market integration.